Cortical visual processing evokes short-latency reward-predicting cue responses in primate midbrain dopamine neurons. Issue 1 (December 2018) - Takakuwa, Norihiro; Redgrave, Peter; Isa, Tadashi
Abstract After classical conditioning dopamine (DA) neurons exhibit short latency responses to reward-predicting visual cues. At least two possible projections could induce such DA responses; the cortical and subcortical visual pathways. Our recent study has shown that after a lesion of the striate cortex (V1), the superior colliculus (SC), a critical node of the subcortical visual pathway, can mediate short latency cue responses in the DA neurons of macaque monkeys. An obvious question then is does the cortical pathway have a similar capacity? Using the monkeys with a unilateral V1 lesion that took part in the preceding study, we recorded DA activity while they were performing the same classical conditioning task. However, in this study conditioned visual stimuli were presented to the intact visual field, and the effects of ipsilateral SC inactivation were examined. We found that after the SC was inactivated by injections of muscimol both conditioned behavioral responding and reward-predicting, short latency ( 100 ms) cue-elicited DA neuronal responses were unaffected These results indicate that the intact cortical visual pathway can also mediate short latency cue elicited responses in DA neurons in the absence of a normally functioning subcortical visual system.